Penerapan Terapi Rendam Kaki Air Hangat Campur Garam dan Serai Pada Pasien Hipertensi di Panti Werdha Dharma Bhakti Palembang - Marcelin Vera Octavia; Sri Indaryati; Novita Elisabeth Daeli (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is a chronic disease characterized by increased arterial blood pressure. Hypertension cannot be avoided, including in vulnerable groups such as the elderly because as age increases, the risk of hypertension increases so appropriate treatment is needed. Hypertension treatment can be done pharmacologically or non-pharmacologically. Non-pharmacological therapy in this case is foot soak therapy in warm water mixed with salt and lemongrass. The aim of the research is to implement warm water foot soak therapy with salt mixed with lemongrass for hypertensive patients into nursing care. The method used was descriptive with a killing process approach in 3 patients with a one group pretest posttest research design. The results of the warm water foot soak therapy mixed with salt and lemongrass showed a reduction in blood pressure, namely Mrs. N from 148/72mmHg to 138/64mmHg, Mrs. /85mmHg. In conclusion, there was a decrease in blood pressure after the foot soak therapy in warm water mixed with salt and lemongrass.